2021
DOI: 10.14305/jn.19440413.2021.13.2.01
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Teacher Shortages in the COVID-19 Landscape: Viewing Teacher Candidates as Assets

Abstract: COVID-19 continues to impose dire consequences on all sectors of our public education system. Many students, particularly those from vulnerable populations, are receiving reduced amounts of direct instruction and are experiencing significant losses in learning. At the same time, educator preparation programs (EPPs) are struggling to ensure that teacher candidates have ample opportunities to apply their newly acquired pedagogical skills in high quality clinical placements. In this article we describe and provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The emphasis of this framework is on K-12 student learning, creating a culture of adult lifelong learning, bidirectionality and mutual benefit. Additionally, it is important to note that the interviews took place during the early stages of the pandemic which heightened the need for school-EPP partnerships in a bidirectional and mutually beneficial way (Darling-Hammond & Hyler, 2020;Rosenberg et al, 2021). The pandemic elevated the need for nurturing and developing school-EPP partnerships and set a tone for the importance of these partnerships and supporting the development of an educational community, creative thinking about learning opportunities, new roles and collaboration (Darling-Hammond & Hyler, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The emphasis of this framework is on K-12 student learning, creating a culture of adult lifelong learning, bidirectionality and mutual benefit. Additionally, it is important to note that the interviews took place during the early stages of the pandemic which heightened the need for school-EPP partnerships in a bidirectional and mutually beneficial way (Darling-Hammond & Hyler, 2020;Rosenberg et al, 2021). The pandemic elevated the need for nurturing and developing school-EPP partnerships and set a tone for the importance of these partnerships and supporting the development of an educational community, creative thinking about learning opportunities, new roles and collaboration (Darling-Hammond & Hyler, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, our EPPs are challenged to respond to emerging expectations and changing needs of schools. We also need EPP designs and policy implementation strategies that address the changing context of the educator workforce and make use of findings from teacher attrition and retention research that reflect the importance of the provision of support, compensation and manageable working conditions to beginning educators (Rosenberg et al, 2021). For example, interns entering the workforce from Generation Z (i.e.…”
Section: Barriers and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently reported school-based challenge was staff shortages; this was the only challenge in this study reported by more than half of the schools and aligns with research highlighting staff shortage problems in school settings. 15 , 16 Students who receive special education services or have underlying health conditions, in particular, might require dedicated support from staff (e.g., paraprofessionals who provide 1-1 support) and might be more acutely impacted by staff shortages. 17 , 18 Staff shortages might have also contributed to schools’ inability to provide adequate virtual supports and accommodations.…”
Section: Discussionmentioning
confidence: 99%